Penerapan Metode Grey Relational Analysis dan Rank Order Centroid dalam Pemilihan Travel Agent - Yuri Rahmanto (PT. Tech Cart Press, 2024)
Choosing a travel agent is an important process for individuals or organizations in determining a travel service provider that can meet their needs with the best quality and competitive prices. Choosing a travel agent is a decision that affects the overall travel experience, whether for business or leisure. In this process, potential customers often face challenges in determining the best travel agent among the many options available. In addition, the presence of subjective reviews from other users and promotional ads that highlight certain advantages often add to the complexity of decision-making. In the face of the many options available, it is important to conduct an objective evaluation so that the decision taken is not only about cost, but also about the quality of service and the reputation of the service provider. The purpose of this study is to apply the Grey Relational Analysis (GRA) and Rank Order Centroid (ROC) methods in the process of selecting the best travel agent to provide recommendations for decision-makers in choosing the best travel agent based on the results of a comprehensive analysis, which integrates both weighting and analysis methods. The results of alternative ranking using a combination of ROC and GRA Agent G occupy the highest position with a value of 0.2525, showing the best performance compared to other alternatives. The second and third positions were filled by Agent A and Agent C, with values of 0.2013 and 0.1914, respectively, which also displayed significant performance.